Способ очистки гексафторида урана от нуклида технеция-99 - Гаврилов П. М. Петр Михайлович; Жерин И. И. Иван Игнатьевич; Короткевич В. М. Владимир Михайлович; Лазарчук В. В. Валерий Владимирович; Ледовских А. К. Александр Константинович; Мазин В. И. Владимир Ильич; Стерхов М. И. Максим Иванович; Торгунаков Ю. Б. Юрий Борисович; Щелканов В. И. Владимир Иванович
опубл. 10.06.08